Analisis Faktor yang Mempengaruhi Earning Management di Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Tahun 2015-2019 - Geni Ramadhani; Citra Ramayani; Nilmadesri Rosya (STKIP PGRI Sumatera Barat, 2021)
This study aims to analyze: The effect of profitability, leverage, company size, managerial ownership, free cash flow on earnings management in manufacturing companies in the consumer goods industry listed on the IDX in 2015-2019. Earnings management is measured by discretionary accruals with the modified Jones model. The population in this study were all manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange with a sample size of 13 companies. The data used in this study are data on manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange in 2015-2019 using panel data regression. The results of this study indicate that profitability has no significant effect on earnings management. Leverage has a significant effect on earnings management. Firm size has no significant effect on earnings management. Managerial ownership has a significant effect on earnings management. Free cash flow has no significant effect on earnings management. Profitability, leverage, firm size, managerial ownership, free cash flow simultaneously have a significant effect on earnings management.Keywords: Profitability, Leverage, Company Size, Managerial Ownership, Free Cash Flow and Earnings Management